Design, Synthesis, and Quantum Chemical Calculations of 2,6-Diphenylspiro[cyclohexane-1,3’-pyrido[1,2-a]pyrimidine]-2’,4,4’-trione through DFT approach - Kumar, Roop; Devi, Poornima; Verma, Anil K.; Bishnoi, Abha (Letters in Organic Chemistry, 2019)
Structural elucidation of synthesized 2,6-diphenylspiro[cyclohexane-1,3’-pyrido[1,2- a]pyrimidine]-2’,4,4’-trione has been done by UV, FT-IR, 1H, 13C NMR and mass spectroscopy. The molecule was further subjected to density functional theory (DFT) studies with B3LYP function using 6-31G(d,p) basis atomic set. The title molecule was investigated on the basis of thermodynamic properties, polarizability, hyperpolarizability, intermolecular interactions, HOMO and LUMO energy values, MESP, ESP and NBO computations to correlate experimental results with in-silico studies.
Keywords: ESP